Aan Widiyono Studi Analisis Pemahaman Guru SD dalam Pembuatan Video Pembelajaran Berbasis ZD Soft Screen Recorder dan Bandicam: Studi Analisis Pemahaman Guru SD dalam Pembuatan Video Pembelajaran Berbasis ZD Soft Screen Recorder dan Bandicam (Adi Widya: Jurnal Pendidikan Dasar, 2023)
Abstract The skills of teachers to make learning videos in the current digital era are very important so that the learning can be carried out according to the needs of students. This study aims to describe the results of the analysis of elementary school teachers' understanding in their ability to make learning videos through the use of the ZD Soft Screen Recorder and Bandicam applications in this pandemic era. The research method used is descriptive qualitative with the subject of elementary school teachers who are in the lotus cluster kkg forum, Jepara district. Data analysis was carried out with data reduction activities, data display and conclusions or data verification. The results of this study indicate the understanding of teachers in making learning videos through applications that are already available in the sufficient category, 70.6% of teachers know about making videos, 29.6% of teachers do not know it. In addition, teachers also do not quite understand how to use the ZD Soft Screen Recorder and Bandicam applications in making learning videos. Third, teachers understand the benefits of making their own learning videos that can support the learning process to be interesting and fun because it can be adjusted to the needs of students, especially applied in distance learning such as the current pandemic era. The results of this analysis can enrich the data and can also be mapped for follow-up activities. Keywords: Teacher's Understanding, Learning Video, ZD Soft Screen Recorder, and Bandicam